Potential effect of marine traffic on white-beaked dolphin (Lagenorhynchus albirostris) distribution and behaviour in Faxaflói Bay, southwest Iceland - Zezza, Letizia (Alma Mater Studiorum - Università di Bologna, 2015)
Faxaflói bay is a short, wide and shallow bay situated in the southwest of Iceland. Although hosting a rather high level of marine traffic, this area is inhabited by many different species of cetaceans, among which the white-beaked dolphin (Lagenorhynchus albirostris), found here all year-round. This study aimed to evaluate the potential effect of increasing marine traffic on white-beaked dolphins distribution and behaviour, and to determine whether or not a variation in sighting frequencies have occurred throughout years (2008 – 2014). Data on sightings and on behaviour, as well as photographic one, has been collected daily taking advantage of the whale-watching company “Elding” operating in the bay. Results have confirmed the importance of this area for white-beaked dolphins, which have shown a certain level of site fidelity. Despite the high level of marine traffic, this dolphin appears to tolerate the presence of boats: no differences in encounter durations and locations over the study years have occurred, even though with increasing number of vessels, an increase in avoidance strategies has been displayed. Furthermore, seasonal differences in probabilities of sightings, with respect to the time of the day, have been found, leading to suggest the existence of a daily cycle of their movements and activities within the bay. This study has also described a major decline in sighting rates throughout years raising concern about white-beaked dolphin conservation status in Icelandic waters. It is therefore highly recommended a new dedicated survey to be conducted in order to document the current population estimate, to better investigate on the energetic costs that chronic exposure to disturbances may cause, and to plan a more suitable conservation strategy for white-beaked dolphin around Iceland.